Information politics, protests, and human rights in the digital age / [edited by] Mahmood Monshipouri. - Monshipouri, Mahmood, 1952- (Cambridge University Press, 2016)
We live in a highly complex and evolving world that requires a fuller and deeper understanding of how modern technological tools, ideas, practices, and institutions interact, and how different societies adjust themselves to emerging realities of the digital age. This book conveys such issues with a fresh perspective and in a systematic and coherent way. While many studies have explained in depth the change in the aftermath of the unrests and uprisings throughout the world, they rarely mentioned the need for constructing new human rights norms and standards. This edited collection provides a balanced conceptual framework to demonstrate not only the power of autonomous communication networks but also their limits and the increasing setbacks they encounter in different contexts.